Evaluation of The Performance of Hot Mix Asphalt with Natural Rubber (Latex) for Asphalt Concrete- Binder Course (AC-BC) - Faradina Utami; Bambang Sugeng Subagio; Aine Kusumawati (Institut Teknologi Bandung, 2020)
This study aims to measure the performance of the Hot Mix Asphalt for Asphalt Concrete Binder Course (AC-BC) with addition of natural rubber (latex) at variations of 0%, 2% and 3% by weight. The method used in this study is an experimental method in a laboratory that consists of natural aggregate testing, rheology testing for asphalt pen 60/70 and asphalt pen 60/70 plus natural rubber (latex) and AC-BC mixture testing. The method used is Marshall Test to obtain optimum asphalt content (OAC) and another method consists of UMATTA Resilient Modulus Test and strain controlled Four Points Fatigue Test. The addition of natural rubber in the AC-BC mixture reduced the optimum asphalt content (OAC) and increased the Marshall stability value, the optimum percentage is 3% natural rubber (latex) with the lowest OAC of 5.4% and the highest Marshall stability. The UMATTA test with 2% natural rubber (latex) resulted in the highest Resilient Modulus value compared to the other two blends. Fatigue testing at strain 500 Î¼Îµ, 600 Î¼Îµ, and 700 Î¼Îµ resulted that the mixture of AC-BC with 3% natural rubber produced the highest fatigue life value compared to the other two mixes. In general, the result of testing and its analysis concluded that the use of natural rubber (latex) can reduce the use of asphalt in the mixture. This can be relified by decreasing the value of OAC in the mixture with natural rubber. The mixture with 3% natural rubber (latex) gives the highest resistance to fatigue cracks in the laboratory.